Quantitative Analysis of Medical Records In Hospitals - Dony Setiawan Hendyca Putra; Athiyyah Yumna; Atma Deharja (Puslitbang Sinergis Asa Professional, 2024)
Incomplete medical records often occur in every hospital, especially in the inpatient department. This still does not meet the hospital's minimum service standards, namely that filling in medical records must be 100% complete. Incompleteness in filling out medical record files will result in the patient's health records being loaded out of sync and the patient's previous health information being difficult to identify. The aim of the research is to identify the completeness of filling in medical record files and the factors that cause incomplete filling in of inpatient medical record files. The method used is a literature review. Literature selection is based on inclusion and exclusion criteria from databases such as Google Scholar, Crossref, Jember State Polytechnic e-Library, and Garuda Portal. The literature used was 19 articles. The research results related to incomplete patient names, date of birth, age, address, gender, doctor's name, date of implementation of patient care, incomplete important reports, incomplete authentication of inpatient medical record files showed quite high results. This incompleteness is due to indiscipline of officers, lack of knowledge about the benefits of complete medical records, lack of training for officers regarding filling out medical records, lack of monitoring and evaluation in filling out medical records. Officers who play a role in filling out medical records are medical personnel including doctors in charge of patients, emergency room doctors, emergency room nurses, inpatient nurses, as well as medical record unit officers who control the completeness of filling in medical records. So the suggestion in this research is the importance of increasing the discipline of doctors and nurses in filling out inpatient medical records, providing rewards and punishments regarding the completeness of filling in medical records.